Trends and Prospects for the Development of the Cereal Market in Ukraine - Oksana Penkova; Andrii Kharenko; Yurii Tsymbaliuk (Науковий вісник Мукачівського державного університету. Серія Економіка, 2020)
The development of agricultural products processing, in particular cereals, and improving their quality characteristics will contribute to the growth of employment in rural areas, satisfaction of internal and external demand, growth of foreign exchange earnings to the state and incomes of commodity producers. The purpose of the paper is to assess the prospects for the development of the cereal products market in Ukraine, considering trends in supply and demand. The methodological basis of the research was system and dialectical approaches and the application of synthesis and analysis methods in determining the regularities and features of the cereal products market in Ukraine. The paper analyses the dynamics and structure of cereals production, identifies the problems of increasing the supply of their main types. Factors of internal and external demand for Ukrainian cereals and future trends in the development of the cereal market are considered. As a result, it is proved that the volume of production of basic cereals directly depends on the availability of raw material supply and its quality, demand for finished products both on the internal market and from importing countries of Ukrainian products, as well as the retrospective profitability of sales of alternative crops. The expansion of sales of Ukrainian cereal products on the internal market can be achieved through the integrated use of non-tariff restrictions that do not contradict agreements within the WTO. The originality of the study consists in systematising the factors of cereal products supply and demand development and analysing their impact on market conditions. The practical significance of the study is to identify the main areas in which problems of further development of the cereal industry are generated, which creates the basis for developing measures to minimise their negative impact